1992
DOI: 10.1021/jf00021a003
|View full text |Cite
|
Sign up to set email alerts
|

Variations of nootkatone and valencene levels during the development of grapefruit

Abstract: The distribution of nootkatone and valencene in grapefruit was determined by gas-liquid chromatography-mass spectrometry (GLC-MS). Changes in the concentration of valencene and nootkatone were observed during the development of fruits, increases in these compounds coinciding with the linear and the maturation steps, respectively. The possible participation of valencene and 2-hydroxyvalencene as precursors in the biosynthetic pathway for nootkatone in grapefruit is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…In the chromatographic conditions used, the retention time (Rt) corresponding to this sesquiterpene was 41.70 min, and its mass spectrum was similar to that obtained in other works (Del Rio et al, 1992a;Del Rio and Ortuiio, 1994).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In the chromatographic conditions used, the retention time (Rt) corresponding to this sesquiterpene was 41.70 min, and its mass spectrum was similar to that obtained in other works (Del Rio et al, 1992a;Del Rio and Ortuiio, 1994).…”
Section: Resultssupporting
confidence: 78%
“…For capillary gas-liquid chromatography-mass spectrometry (GLC-MS) a Hewlett-Packard 5993 mass spectrometer was used with a column similar to that used above. The injector and transfer line temperature was 255 "C, ionization energy 70 eV, and scan time 1 s. Peak identification was confirmed by comparing the retention time and mass spectrum with those of authentic sample, as described previously (Del Rio et al, 1992a). Quantitative determinations were based on the known amount of added standard.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthetic route to (+)-nootkatone in grapefruit has not been established experimentally, but has been suggested to start from valencene on which a regioselective allylic hydroxylation results in formation of 2-hydroxyvalencene (or nootkatol), followed by oxidation to (+)-nootkatone [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies 21,25,26 report that these compounds are formed in the flavedo in increasing levels as the fruit matures. Coggins et al 25 examined the changes in essential oil constituents from the peel of Navel oranges, with and without gibberellin treatment.…”
Section: Ultimate Value Of Valencenementioning
confidence: 93%
“…They found that valencene concentrations in the untreated fruit generally increased with increasing maturity, which maximized at 350% higher concentrations than when the fruit was first examined. del Rio et al 26 observed the development of valencene and nootkatone in grapefruit as the fruit was allowed to mature. They observed that after 9 weeks valencene levels began to increase and reached a maximum level of approximately 1 mg/100 g fresh weight wax column, only those compounds with similar wax LRI values are considered.…”
Section: Ultimate Value Of Valencenementioning
confidence: 99%